Total synthesis of (+)-isolaurepan - Tripathi, Divya; Kumar, Pradeep (Tetrahedron Letters, 2008)
A versatile and efficient method for the enantioselective synthesis of 2,7-cis-disubstituted oxepane 1c, (+)-isolaurepan, using oxidative resolution of a secondary alcohol and highly diastereoselective Et(3)SiH/TMSOTf-promoted reductive cyclization of a hydroxy ketone is described. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cis-selective cyclization; Cyclic ethers; Isolaurepan; Oxepanes; Oxidative resolution of secondary alcohols

General approach to medium-sized ring ethers via hydrolytic and oxidative kinetic resolutions: stereoselective syntheses of (-)-cis-lauthisan and (+)-isolaurepan - Tripathi, Divya; Pandey, Satyendra Kumar; Kumar, Pradeep (Tetrahedron, 2009)
A short and enantioselective approach to medium ring ethers and its application to the syntheses of (-)-cis-lauthisan and (+)-isolaurepan are described. The synthetic strategy features Jacobson's Hydrolytic Kinetic Resolution (HKR), oxidative resolution of secondary alcohol, and highly diastereoselective Et(3)SiH/TMSOTf-promoted reductive cyclization of a hydroxy ketone to give exclusively the different medium-sized cis-disubstituted cyclic ethers. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: cis-Reductive cyclization; Jacobson's Hydrolytic Kinetic Resolution (HKR); Oxepanes; Oxidative resolution of secondary alcohol; Ring ether